Cytotoxic Effects of Plant Growth Extracts Temu Giring (Curcuma Heyneana) and Temu Ireng (Curcuma Aeruginosa) against Several Cancer Cells - Sri Atun; Nurfina Aznam; Retno Arianingrum; Sri Nurestri (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The purpose of this study is to investigate the cytotoxic activity of extracts and fractions of the rhizoma from temu giring and temu ireng against some cancer cells, such as breast carcinoma cells (MCF-7) and cervical carcinoma (Ca Ski). The research method is to do with experiments in the laboratory which includes extraction and fractionation of compounds from the rhizome from temu giring and temu ireng, test the cytotoxicity against cancer cells Breast carcinoma (MCF-7) and cervical carcinoma (Ca Ski). Test results on the activity of extracts and fractions from tubers from temu giring and temu ireng on breast carcinoma (MCF-7); Cervical carcinoma (Ca Ski) showed good activity (below 100 µg/ml), except the methanol extract temu ireng which shows the IC50 upper of 100 µg/ml. This indicates that the extracts from temu giring and temu ireng great potential for development as anticancer drug.Keywoods: Curcuma heyneana; Curcuma aeroginosa; cytotoxic effect; anticancer